Hibah dalam Sengketa Harta Bersama: Kajian Putusan Pengadilan Agama dalam Perspektif Maqashid Syariah - muhammad Aulia Rahman; Adied Najiyurrahman; Agustina Rahayu Husein (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
While previous studies on joint marital asset disputes have examined evidentiary issues or distributive justice separately, none have simultaneously integrated evidentiary law, the Compilation of Islamic Law (KHI), and the three dimensions of Islamic justice (legal, moral, social) in a case involving an unsubstantiated gift (hibah) claim. This study fills that gap by analyzing a final and binding Religious Court decision rendered by the Jombang Religious Court, selected based on inclusion criteria (absence of a prenuptial agreement, asset acquisition during marriage, and a hibah claim lacking formal proof). Using normative legal research with a case approach, the analysis was operationalized through grammatical, systematic, and teleological interpretation of Articles 35 (Marriage Law), 87, and 97 KHI. The findings reveal three novel insights. First, the judges placed the entire burden of proof on the party claiming hibah; the absence of qabdh (physical delivery of the gifted object), a written hibah deed, or witnesses rendered the claim legally unsubstantiated. Consequently, the principle of gemeinschaft van goederen (automatic asset commingling upon marriage) remained the default legal starting point, leading to a 50:50 division under Article 97 KHI. Second, a normative tension emerges: although Article 87 KHI recognizes hibah as separate property, in evidentiary practice, an unproven hibah claim reverts to the 50:50 presumption, effectively subordinating Article 87 to Article 97. Third, the decision aligns with al-'adl by prioritizing legal objectivity, recognizing non-economic spousal contributions, protecting economically vulnerable ex-spouses, and safeguarding property (hifz al-mal) as a core objective of maqashid sharia.